Edukasi Nilai Ekonomi Hindu untuk Menumbuhkan Kebiasaan Menabung Anak di Dusun Alas Malang - Wijayanti, Ni Putu Aryani Sintia; Suarna, I Nyoman; Sudarsini, Ni Nengah; Amni, Sri Sofiana; Yasa, I Komang Widya Purnama (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Saving habits are a fundamental aspect in shaping a thrifty, disciplined, and responsible character from an early age. However, in Dusun Alas Malang, awareness of the importance of saving remains low, especially among children. Through an individual Community Service Program (KKN), an educational and training-based activity was carried out to foster saving habits among elementary school students. The methods used included delivering learning materials, practicing decorating piggy banks made from recycled materials using origami paper, and conducting a question-and-answer session as an evaluation. Hindu economic values from Sloka Sarasamuccaya 262 were integrated to relate the concept of saving with religious teachings. The results showed an increase in children’s understanding and enthusiasm for saving pocket money, along with improved creativity through piggy bank decoration activities. This program effectively fostered frugality, creativity, and financial as well as moral responsibility. Early saving education is essential to build children’s awareness of financial management.